A PRELIMINARY EPIDEMIOLOGICAL INVESTIGATION ON LEUKEMIAS AND LYMPHOMAS IN MAZANDARAN PROVINCE (NORTH OF IRAN) - M. Bagheri; M. Mahmoudi; F. Alaeddini; A. Nadim (Tehran University of Medical Sciences, 1999)
Cancer in all forms caused 9% of deaths throughout the world. In the developed countries it is the second ranking cause of death and in the developing countries it is ranked fourth as the cause of death. In Iran, cancer ranks third as the cause of death. The second most prevalent types of cancer in Iran were lymphoma and leukaemia (L&L). The estimated incidence of L&L in 1952 was 0.66 per 100,000 populations. Our prime interest was to determine the L&L incidence rate and also to identify some of the risk factors related to L&L. Mazandaran was selected because there was an ongoing program of registry conducted by Babol Research Station of the IPHR. In the first part of this study, the geographical distribution of all cases seen since 1992 in this province was identified. The second part was a population-based matched case-control study to identify some of the risk factors of these cancers. 257 patients of all types of L&L were selected with the same number of controls. 648 cases of leukemia and lymphoma in Mazandaran were found in cancer registry from 1992 to 1997. In all types, the male to female ratio was almost 1.5. No significant association was found with the factors studied except for history of drug addiction which is true for adult patients. The study shows the importance of leukaemia and Lymphoma as important public health problems in this province. As these areas are the main centres of growing rice in the country, there is the possibility of some association of L&L with the types of insecticides and herbicides used.